PINISI ETHNOMATHEMATICS: PHILOSOPHICAL VALUES AND APPLICATION OF MATHEMATICAL CONCEPTS IN PINISI SHIPBUILDING IN ARA VILLAGE, BONTOBAHARI DISTRICT, BULUKUMBA REGENCY - Kathina Wardhani; Kyra Audrey Nevely; Vanness Jefferson Ho; Matthew Laudi; Sean Sabian; Kadek Irayasa; Edward Wijaya (Politeknik Pariwisata Makassar, 2025)
Abstract This research discusses the application of mathematical concepts and philosophical value of the pinisi ship which specifically explored the geometrical shape and transformation aspect. This is a qualitative study using an ethnographic approach. In addition, data collection techniques were collected through observation, interviews, and documentation. The informants are Punggawa and Sawi. This study uses the Miles and Huberman data analysis technique, consisting of data reduction, data display, and conclusions drawing. The result of this study reveals that on the Pinisi ship there are several mathematical shapes such as triangles, trapezoids, rectangles, and cylinders. Meanwhile, geometric transformation can be found in tambugu, soloro, anjong, tiang agung (great masts), tanpasere sails, and other components. Generally, the shape and geometric transformations can be associated with the philosophical meaning of the Pinisi ship. In this case, it is closely related to religious symbols and the human body. Keywords: Ethnomathematics, Pinisi, and Philosophical